Topological surface state of α-Sn on InSb(001) as studied by photoemission - Scholz, MR; Dudy, L; Reis, F; Adler, F; Aulbach, J; Collins-McIntyre, LJ; Duffy, LB; Yang, HF; Chen, YL; Hesjedal, T; Liu, ZK; Hoesch, M; et al. (American Physical Society, 2018)
We report on the electronic structure of the elemental topological semimetal α − Sn on InSb(001). High-resolution angle-resolved photoemission data allow us to observe the topological surface state (TSS) that is degenerate with the bulk band structure and show that the former is unaffected by different surface reconstructions. An unintentional p -type doping of the as-grown films was compensated by deposition of potassium or tellurium after the growth, thereby shifting the Dirac point of the surface state below the Fermi level. We show that, while having the potential to break time-reversal symmetry, iron impurities with a coverage of up to 0.25 monolayers do not have any further impact on the surface state beyond that of K or Te. Furthermore, we have measured the spin-momentum locking of electrons from the TSS by means of spin-resolved photoemission. Our results show that the spin vector lies fully in-plane, but it also has a finite radial component. Finally, we analyze the decay of photoholes introduced in the photoemission process, and by this gain insight into the many-body interactions in the system. Surprisingly, we extract quasiparticle lifetimes comparable to other topological materials where the TSS is located within a bulk band gap. We argue that the main decay of photoholes is caused by intraband scattering, while scattering into bulk states is suppressed due to different orbital symmetries of bulk and surface states.